POTRET POLITIK GENDER DI NTB: Kegagalan Caleg Incumbent DPRD Provinsi pada Pemilu 2019 - Ibnu Murtadho; hairurrayan (Politea : Jurnal Politik Islam, 2022)
The writing of this paper aims to find out the problem of women's political representation in the Provincial DPRD of NTB in 2019. To examine the results of this study, social theory was used to answer how the factors that caused the fail incumbent of the female legislative candidates provincial DPRD in general election 2019 structurally and culturally. This study uses a behavioral approach, with two data sources, primary data sources and secondary data sources. Sources of primary data obtained from observations, interviews with the people concerned in the research according to the research focus, and documentation. There are three informants in this study who are incumbent of the female legislative candidates who failed to occupy the 2019 Provincial DPRD seats from the PKB party Hj. Nurlaela, the Democratic party Hj. Misfalah, and the Nasdem party Hj. Suryahartin. The results of this study indicate that the fail incumbent of the female legislative candidates provincial DPRD in general election 2019 is caused by three factors including: system constraints faced by Hj. Suryahartin, socio-cultural problems faced by H. Nurlaela, and economics or psychology faced by Hj. Misfalah points out that political system constraints are an obstacle to female legislative candidates who fail to occupy seats as members of the Provincial People's Legislative Assembly. This is influenced by several factors, both external and internal.